KONSEP DAN SISTEM NILAI DALAM PERSFEKTIF AGAMA-AGAMA BESAR DI DUNIA - Uqbatul Khair Rambe (UIN Sumatera Utara, 2020)
Value as a driving force in life, which gives meaning and validation to one's actions. Values held in both intellectual and emotional terms. The combination of these two dimensions determines something that is worth functioning in life. If in giving meaning and validation to an action, it is not small, while not more intellectual, the combination is called the norm or principle. Norms or principles such as faith, justice, brotherhood and others become values that are agreed upon in the patterns of behavior and patterns of thinking of a group, while universal norms are determined, while special and comparable values for each group. Value is the essence that is attached to something that is very important for human life, especially regarding the goodness and acts of kindness of a thing, the value of the meaning of the traits or things that are important or useful for welfare. Value is something abstract, ideal, value is not a concrete thing, not a fact, it is not only a matter of right and wrong that demands empirical proof, it needs social appreciation that is desired, liked, and disliked.Keywords: Concepts, Values, Great Religions In The World.